Indonesia's Response to the Rise of Anti-Asian Hate Racial Discrimination in the United States in 2020-2021 in a Human Security Perspective - IYANDRAPUTRA, YOSIA OCTAFREIRA; Sidik, Hasan; Yulianti, Dina (Universitas Padjadjaran, 2026)
From the colonial era to the contemporary period, the history of the United States (US) has recorded many cases of racism, although in the 20th century the Civil Rights Movement ended legal segregation. Cases of racism strengthened again in 2020–2021 targeting Asians in the US, including Indonesian citizens, after Covid-19 was referred to as the